2019
DOI: 10.1002/ecy.2837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil heterogeneity and endogenous processes on plant spatial structure

Abstract: Within communities, organisms potentially self‐organize through endogenous processes that create nonrandom spatial structure as they interact with one another or modify the abiotic environment. In contrast, exogenous processes such as environmental heterogeneity or variable immigration are thought to be dominant processes controlling these spatial patterns. Although both endogenous and exogenous processes likely occur, their relative importance is still largely unknown because of limited analytical tools and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Abiotic and biotic processes were shown to act simultaneously and to interact in many plant populations (e.g. Adler et al, 2007;Chase and Myers, 2011;Chisholm and Pacala, 2010; Filho et al, 2012;Furniss et al, 2017;Getzin et al, 2008;John et al, 2007;Legendre et al, 2009;Mitchell et al, 2017;Schouten and Houseman, 2019;Shen et al, 2013;van Waveren, 2016). Because both abiotic and biotic processes can result in similar spatial patterns of individuals, it can be challenging, yet not impossible, to study the relative importance of biotic and abiotic processes and disentangle possible interactions.…”
Section: Index Of Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Abiotic and biotic processes were shown to act simultaneously and to interact in many plant populations (e.g. Adler et al, 2007;Chase and Myers, 2011;Chisholm and Pacala, 2010; Filho et al, 2012;Furniss et al, 2017;Getzin et al, 2008;John et al, 2007;Legendre et al, 2009;Mitchell et al, 2017;Schouten and Houseman, 2019;Shen et al, 2013;van Waveren, 2016). Because both abiotic and biotic processes can result in similar spatial patterns of individuals, it can be challenging, yet not impossible, to study the relative importance of biotic and abiotic processes and disentangle possible interactions.…”
Section: Index Of Tablesmentioning
confidence: 99%
“…Because both abiotic and biotic processes can lead to similar spatially clustered patterns, there is a long-lasting and ongoing discussion about the relative importance of the two contrasting processes and how to disentangle them in plant populations (e.g. Adler et al, 2007;Chase and Myers, 2011;Chisholm and Pacala, 2010;Diniz-Filho et al, 2012;Furniss et al, 2017;John et al, 2007;Legendre et al, 2009;Mitchell et al, 2017;Schouten and Houseman, 2019). While biotic processes including competition (Coates et al, 2009;Wang et al, 2010a), limited seed dispersal (Martínez and González-Taboada, 2009) ENVIRONMENTAL…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contradicting this conceptual framework, recent studies suggest that soil heterogeneity may affect plant distribution at the same spatial scales where biotic interactions take place (Luzuriaga, González, & Escudero, 2015; Mudrák et al, 2016; Schouten & Houseman, 2019; Tamme, Gazol, Price, Hiiesalu, & Pärtel, 2016). Indeed, strong relationships between soil variation and species distribution at relatively fine scales have been found in tropical forests (Baldeck et al, 2013; Chang, Zelený, Li, Chiu, & Hsieh, 2013; John et al, 2007; Xia, Chen, Schaefer, & Detto, 2015), and some authors have shown the effects of fine‐scale environmental heterogeneity on plant responses (Hutchings, John, & Stewart, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, strong relationships between soil variation and species distribution at relatively fine scales have been found in tropical forests (Baldeck et al, 2013; Chang, Zelený, Li, Chiu, & Hsieh, 2013; John et al, 2007; Xia, Chen, Schaefer, & Detto, 2015), and some authors have shown the effects of fine‐scale environmental heterogeneity on plant responses (Hutchings, John, & Stewart, 2000). Note, however, that plants can also modify soil conditions generating fine‐scale spatial or temporal heterogeneity (Ehrenfeld, Ravit, & Elgersma, 2005; van Breemen, 2013), whose effect, without experimental studies, cannot be separated of heterogeneity caused directly by the soil abiotic factors (Schouten & Houseman, 2019). Therefore, until recently, neither the effects of fine‐scale environmental, and particularly soil, heterogeneity on community assembly (Baldeck et al, 2013; Letten, Keith, Tozer, & Hui, 2015; Tamme et al, 2016) nor their role on the spatial distribution of individual species within the community have been explicitly considered (Shen et al, 2013; Xia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%